Ag Nanoparticles/α-Ag2WO4 Composite Formed by Electron Beam and Femtosecond Irradiation as Potent Antifungal and Antitumor Agents - Assis, M; Robeldo, T; Foggi, C C; Kubo, A M; Mínguez-Vega, G; Condoncillo, E; Beltran-Mir, H; Torres-Mendieta, R; Andrés, J; Oliva, M; Vergani, C E; Barbugli, P A; et al. (Scientific reports, 2019)
The ability to manipulate the structure and function of promising systems via external stimuli is emerging with the development of reconfigurable and programmable multifunctional materials. Increasing antifungal and antitumor activity requires novel, effective treatments to be diligently sought. In this work, the synthesis, characterization, and in vitro biological screening of pure α-Ag2WO4, irradiated with electrons and with non-focused and focused femtosecond laser beams are reported. We demonstrate, for the first time, that Ag nanoparticles/α-Ag2WO4 composite displays potent antifungal and antitumor activity. This composite had an extreme low inhibition concentration against Candida albicans, cause the modulation of α-Ag2WO4 perform the fungicidal activity more efficient. For tumor activity, it was found that the composite showed a high selectivity against the cancer cells (MB49), thus depleting the populations of cancer cells by necrosis and apoptosis, without the healthy cells (BALB/3T3) being affected.
Keywords: BALB 3T3 Cells; Humans; Oxides; Tumor Cells, Cultured; antifungální látky; wolfram; Electrons; Antineoplastic Agents; lidé; Tungsten; zvířata; proliferace buněk; myši; kovové nanočástice; Silver; Mice; apoptóza; nádorové buňky kultivované; xenogenní modely - testy protinádorové aktivity; Metal Nanoparticles; nádory močového měchýře; Antifungal Agents; stříbro; buňky BALB 3T3; Cell Proliferation; protinádorové látky; oxidy; Xenograft Model Antitumor Assays; Candida albicans; Animals; Urinary Bladder Neoplasms; elektrony; Apoptosis